Rape and Sexual Violence in the ICJ's Judgment in Croatia v. Serbia. (30th October 2015) - PECORELLA, GIULIA
Abstract: This article examines the approach followed by the International Court of Justice in Croatia v. Serbia in relation to rape and sexual violence as acts of genocide under Article II of the Genocide Convention. It is argued that this decision leaves much uncertainty with respect to the elements constituting the actus reus of genocide. First, the Court has narrowed the interpretation given by the ad hoc tribunals to what constitutes 'serious harm' under Article II(b). Second, it has introduced an objective requirement, which is in fact unnecessary under Article II(c) of the Convention. Third, it seems that, according to the Court, in order for rape and sexual violence to be regarded as genocidal conduct within the meaning of Article II(d) of the Convention, it is necessary to prove that such conduct did in fact prevent births at least within a part of the group.